A review of tourism and hospitality studies on behavioural economics. Issue 3 (May 2022) - Li, ShiNa; Liu, Yixin; Dai, Shanshan; Chen, Mengxin
Tourists display bounded rationality when they rely on heuristics to simplify complex decisions or make decisions not based purely on self-interest. Behavioural economics, which moves beyond the widely criticised assumptions that traditional economics makes regarding rational economic behaviour, provides useful theoretical foundations and approaches to tourism and hospitality studies. This paper reviews and discusses studies that evaluate bounded rational behaviour in the tourism and hospitality industry and examine influencing psychological factors. A review framework of economic behaviour is proposed to identify new perspectives and approaches to evaluating tourists' complex decision-making processes. The paper also considers the prospects for applying behavioural economics theories to tourism and hospitality. It is suggested that limited attention and projection bias should be further examined in future research. The application of anchoring, mental accounting, nudge theory and neuroeconomics to tourism studies is also recommended.